Division Vii: the Galactic System - Hatzidimitriou, Despina; Wyse, Rosemary; Gerhard, Ortwin; Carraro, Giovanni; Elmegreen, Bruce Gordon; Nordström, Birgitta (2012)
Division VII provides a forum for astronomers studying the Milky Way as a galactic system, as well as its constituents. It acts as an umbrella for two commissions, Commission 33 and Commission 37.